Study of obstetric and fetal outcomes associated with maternal perception of decreased fetal movements in third trimester - Padore, Ishaan S.; Jinturkar, Anagha A. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2024)
Background: Prevalence of decreased fetal movement in third trimester has been reported as 4-15% in various studies. Association between maternal perception of decreased fetal movement and poor perinatal outcome like fetal growth restriction, oligohydramnios, fetal distress, preterm births, fetal congenital anomalies, and stillbirth are revealed in different studies. However, decreased fetal movements may sometimes cause unnecessary anxiety to pregnant women or clinicians leading to unnecessary interventions. Keeping this background, we planned to assess the significance of decreased fetal movement perception in third trimester of pregnancy and its correlation with the perinatal outcome. Methods: A prospective observational study was carried out at a tertiary health care center B. J. Government Medical College, Pune for a period of 12 months (October 2021-October 2022). Study included 150 mothers with decreased fetal movement in the third trimester. These mothers were monitored till delivery by Repeat fetal movement count, cardiotocography (CTG), ultrasonography (USG), biophysical profile (BPP) and Doppler studies. Mothers were investigated for identification of ante-natal risk factors and their mode of delivery was noted. APGAR score of neonates at birth, birth weight and requirement of neonatal intensive care unit (NICU) admissions were also noted. Results: Study observed that most of these females were primi-mothers belonging to lower socio-economic class. Oligohydramnios, obesity, gestational diabetes and anemia were observed as common risk factors. Emergency caesarean section was required in one out of five cases while one fourth of these mothers delivered pre-term. Most common neonatal complication observed was intra-uterine growth restriction. Mortality rate was 2%. Conclusions: We thus conclude that mothers with reduced fetal movements are a risk group and should be referred immediately. Overall outcome was good in these babies, when given optimum institutional care.